2014
DOI: 10.1002/ange.201310635
|View full text |Cite
|
Sign up to set email alerts
|

Designing p‐Type Semiconductor–Metal Hybrid Structures for Improved Photocatalysis

Abstract: A practical strategy is proposed to facilitate the migration of holes in semiconductor (the low rate of which limits photocatalytic efficiency) by taking advantage of the Schottky barrier between p‐type semiconductor and metal. A high work function is found to serve as an important selection rule for building such desirable Schottky junction between semiconductor surface facets and metal. The intrinsic charge spatial distribution has to be taken into account when selecting the facets, as it results in accumula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(28 citation statements)
references
References 14 publications
1
27
0
Order By: Relevance
“…Cu 2 O cube with a wide absorption region could be excited by the ultraviolet and visible light in a wavelength range of 200–700 nm, producing photogenerated electron‐hole pairs. Then photogenerated holes can transfer to supported Pd through the {100} facets of Cu 2 O cube, leaving the electrons in the Cu 2 O . The opposite transfer situation of photogenerated carriers alters the electron density on Pd, leading to the distinct activity change of Pd NP‐TiO 2 NS and Pd NP‐Cu 2 O cube under energetic light illumination.…”
Section: Resultsmentioning
confidence: 99%
“…Cu 2 O cube with a wide absorption region could be excited by the ultraviolet and visible light in a wavelength range of 200–700 nm, producing photogenerated electron‐hole pairs. Then photogenerated holes can transfer to supported Pd through the {100} facets of Cu 2 O cube, leaving the electrons in the Cu 2 O . The opposite transfer situation of photogenerated carriers alters the electron density on Pd, leading to the distinct activity change of Pd NP‐TiO 2 NS and Pd NP‐Cu 2 O cube under energetic light illumination.…”
Section: Resultsmentioning
confidence: 99%
“…Wang and co‐workers observed that the Cu 2 O cuboctahedrons with both (1 0 0) and (1 1 1) facets exhibited three times higher in coefficient of photocurrent than the Cu 2 O cubes with solo (1 0 0) or (1 1 1) facets. The unique electronic structure of (1 0 0) facet causes a higher work function (approx.…”
Section: Metal Oxide Substrates Metal/oxide Interfaces and Their Camentioning
confidence: 99%
“…It is generally believed that photocatalysts exhibit better catalytic properties when more active crystal facets are exposed to reacting molecules. [18,19] In many classical photocatalytic semiconductors, it has been shown that controlling the exposure of a suitable crystal facets is an effective strategy to improve photocatalytic performance, for example: TiO 2 , [20,21] BiVO 4 , [22][23][24] Cu 2 O, [25,26] and CeO 2 . [27] In photocatalytic reactions, the high recombination rate of photogenerated electrons and holes is a major factor limiting its photocatalytic performance.…”
Section: Introductionmentioning
confidence: 99%